VITAMIN D STATUS IN A HEALTHY TUNISIAN POPULATION - BAHLOUS, Afef; KRIR, Asma; MRAD, Mehdi; Mouna, BOUKSILA; Safa, KALAI; Osman, KILANI; Elhem, CHEOUR EL KATEB; Nizar, LAADHARI (Journal of Medical Biochemistry, 2022)
Vitamin D deficiency is one of the most common medical conditions worldwide. In Tunisia, several studies evaluated Vitamin D status, but this was concerning specific populations (pregnant women, obese or diabetic patients and children with asthma). The only study that evaluated Vitamin D status in a healthy Tunisian population was conducted by Meddeb and al. in 2002. The update of data available, based on the currently recommended limits, is necessary. This study aimed to estimate the prevalence of hypovitaminosis D in a healthy Tunisian population, and correlate the values with potential risk factors. It was conducted on 209 Tunisian healthy subjects. Data collected included clinical characteristics and dietary intakes. We measured 25-hydroxyvitamin D (25(OH)D), parathyroid hormone (PTH), glycemia, creatinine, calcium, phosphorus, proteins and alkaline phosphatase levels. Hypovitaminosis D was retained for 25(OH)D concentrations <30ng/ml. Vitamin D deficiency was defined by 25(OH)D concentrations <10 ng/ml. The prevalence of hypovitaminosis D and vitamin D deficiency were respectively 92.3% and 47.6%. The main factors that were significantly associated with low vitamin D levels in our multivariate analysis were veiling, living in rural areas and sunscreen use. However, sex, age, socioeconomic level, phototype, solar exposure score, smoking and bone mass index, were not statistically associated with hypovitaminosis D. The study of relationship between vitamin D status and serum PTH levels showed a significative and negative correlation (p< 0.005). Given the high prevalence of vitamin D, an adapted health policy is essential. A widespread vitamin D supplementation and food fortification seems to be necessary in Tunisia.